Investigation of the effects of volleyball training on athletes' liver enzymes and muscle damage markers - Erdogan, R. (Journal of Pharmaceutical Research International, 2021)
Aims: It is seen that regular exercises cause physiological changes in the organism. The effects of such a training are not known especially on liver enzymes and muscle damages. In this regard, this study aimed to determine the effects of long-term volleyball training on athletes` indicators of liver enzymes and muscle damages.